Effect of Gd and Nb co-substitution on enhancing the thermoelectric power factor of nanostructured SrTiO3. Issue 3 (1st February 2021) - Yalini Devi, N.; Vijayakumar, K.; Rajasekaran, P.; Alagar Nedunchezhian, A.S.; Sidharth, D.; Masaru, Shimomura; Arivanandhan, M.; Jayavel, R.
Abstract: Oxide thermoelectric materials have attracted researchers in recent decade due to their attractive features such as low toxicity, low cost and high chemical robustness. Perovskite based oxide thermoelectric are considered as the promising materials, especially for high temperature thermoelectric applications. In the present work, pure SrTiO3, Sr1-x Gdx TiO3 (0 < x < 0.09) and Sr1-x Gdx Ti1-y Nby O3 were prepared by varying Gd concentration (0 < x < 0.09) using hydrothermal method. The XRD analysis confirmed the high crystalline cubic structured nanocomposite with Gd and Nb substitution. The FESEM images revealed cubic morphology of the particles and the size of the cubes varied with the concentration of the dopant. The chemical compositions of the samples were confirmed by EDX analysis. The binding states and elemental composition of the samples were analyzed by XPS. Both the pure SrTiO3, Sr1-x Gdx TiO3 samples show low electrical resistivity and the co-substituted sample exhibited relatively high resistivity. Seebeck coefficient of the samples increased with Gd concentration. The Gd and Nb co-substituted sample shows relatively higher Seebeck coefficient value compared to Gd substituted samples. The power factor of the nanocomposite were calculated from the obtained Seebeck coefficient and resistivity; Gd and Nb co-substituted sample shows relatively high power factor of 311.7 × 10 −6 Wm −1 K −2 at 550 K compared to other samples. Graphical abstract: Image 1 Highlights: Sr1-x Gdx TiO3 (0<x<0.09) and Sr1-x Gdx Ti1-y Nby O3 were prepared by varying Gd concentration using hydrothermal method. Cubic morphology of the samples confirmed by FESEM images and the size of cubes decreased for the co-substituted samples. Sr0.91 Gd0.09 TiO3 shows high power factor of 309.3 ×10 -6 Wm -1 K -2 at 550K compared to other Sr1-x Gdx TiO3 samples. The Gd and Nb co-substituted sample shows higher power factor of 311.7 ×10 -6 Wm -1 K -2 at 550K compared to other samples.